Fruit consumption among university of Ibadan students, Nigeria (2011)
Fruit consumption among undergraduate students was assessed in Ibadan, Oyo State, Southwest. Nigeria, The objectives of the study were to determine the proportion of students' income spent on fresh fruits and processed fruits; determine the level of acceptability of processed fruits by students and the factors affecting the consumption fresh and processed fruits, One hundred students were selected for the study using random sampling technique and data collected using well structured questionnaires, Data obtained was subjected to descriptive and regression analysis, The result of the study show that out of N6487 ,09 earned by students on the average, 4,58%, 4.4% and 9,29% of it were spent on fresh, processed and both kinds of fruits respectively. Majority of students made their choice on fruit consumption based on the prices in the market. Also, more than 60% of the respondents preferred the fresh fruits to processed fruits, Students income and taste were significant determinants of the amount spent on fresh fruits by students (P<O,05), On the other hand. Only students income (P<O,05) had significant effect on the quantity of processed fruit consumed. Based all the findings of this study, stakeholders should be encouraged to employ technique of preserving fresh fruits due to the preference shown for fresh fruits over processed product.